(untitled) (Fiep Bulletin - online, 2014)
Water polo is a collective sport and efforts of high intensity are made in less duration and the skill that is used for the majority of the game is swimming. the objective of this study is to demonstrate that training for water polo athletes is most effective when done always in the presence of the ball, as the ball-handling does not adversely affect the timing. eleven well-trained competitive athletes were recruited and asked to swim the test of the 300 fastest (15 reps of 20 meters), one time with ball, and one time without ball. results can be read in correlation to athletes’ anamnesis, revealing that incidence of ball-handling is signifi cant only in athletes who have a swimming-oriented athletic history, but there are not signifi cant differences in times for athletes who have a water polo-oriented athletic history. some water polo athletes realized systematically smaller times when they swim with ball. the results show as this study can help the coach to train the team for improving the analyzed skills in different mode, creating a methodological system training to enhance the performance. coaches are suggested to carefully monitor swimming rhythm during trials, and to increment ball-handling in every training condition.